Understanding facial recognition disorders in children : prosopagnosia management strategies for parents and professionals - Mindick, Nancy (Jessica Kingsley Publishers, 2010)
Mindick provides an explanation of the types, causes, and characteristics of prosopagnosia. Providing an insider's perspective on the condition, she suggests ways to recognize the signs of facial recognition difficulties in children, and offers specific ideas for ensuring that they are properly supported in their learning and social development.